Mitigating Corruption in Sub-Saharan Africa: Does Heterogeneity in Corruption Levels Matter?. (4th March 2022) - Amegavi, George Babington; Quarshie, Abigail; Mensah, James Kwame
Abstract : In line with Africa's Agenda 2063 goal 12 of improving governance and building accountable institutions, this article contributes to the literature by examining corruption determinants using survey data from the Afrobarometer. Quantile regression estimates across 31 sub-Saharan African countries show that the effects of the determinants of corruption are heterogeneous across the quantiles. We observe that press freedom, parliamentary oversight, and human development have a reducing effect on corruption, whereas government size, ethnic fractionalization, and bureaucratic quality appear to exert a significant positive effect on corruption. Given the heterogeneity in findings, the "one size fits all" strategy in fighting corruption could be inadequate in mitigating corruption in SSA.